Перетворення бізнес моделі на моделі мереж Петрі - Ахмадікатоулі, Аліасгхар (Видавництво Львівської політехніки, 2011)
This paper presents a methodology to transform business designs written in SBVR into petri nets models. This helps business people in an organization have no knowledge of formal language understand the semantic of business rules in graphical representations. Business rules are clearly important because these business rules govern functions and resources in a business process. These rules also enable applications flexible and amenable to change in an information system. This approach presented here aims to transform rules and business vocabularies by distinguish between different rules into petri nets. On the basis of this transformation we are able to accomplish the verification of given rules.
Keywords: Business Process Modeling; Business Rude Modeling; Business rule; SBVR; Petri nets